Trouble in blue - Long, Beverly (Long, Beverly. Heroes of the Pacific Northwest, 2022)
"In a small tourist town, police chief Marcus Price must be suspicious of strangers--especially newcomer Erin McGarry. A series of surprise attacks makes him believe someone wants her out of the way. But who has she crossed? What secrets is she keeping? Avowed bachelor Marcus needs to protect Erin yet resist his attraction to her if both are to survive a killer's terrifying plot."--Back cover.